The role of the technical standard of roads due to traffic safety at nighttime - Zielinkiewicz, Arkadiusz (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
Accident statistics and previous research directly indicate an increased accident risk during deterioration of natural lighting conditions. This increased risk is mainly determined by so-called “human impact”, connected with perception limitations and recognition of situations by nighttime traffic participants. Proper road infrastructure solutions are essential for improvement of driver’s road vision at nighttime. Planning of such solutions requires proper identification of set of accident risk determinants at nighttime. In this paper the attempt to identify of such determinants was performed and the hypothesis that the technical standard of roads is the main infrastructural determinant influencing accident risk at nighttime was verified. Validity of this assumption results from the fact that lower technical standard accompanies lower requirements regarding limits of geometrical parameters, roadside equipment and access control. Thus, with lower technical standard, problems concerning the influence of infrastructure on road safety should appear, especially during nighttime conditions. On the basis of regression accident estimation models, main infrastructural determinants of higher accident risk at nighttime were identified and some design recommendations were formulated.